Prenatal Maternal Stress and the Risk of Asthma in Children - Douros, Konstantinos; Moustaki, Maria; Tsabouri, Sophia; Papadopoulou, Anna; Papadopoulos, Marios; Priftis, Kostas N. (Frontiers in Pediatrics, 2017)
Emerging evidence indicate that maternal prenatal stress (MPS) can result in a range of long-term adverse effects in the offspring. The underlying mechanism of MPS is not fully comprehensible. However, its complexity is emphasized by the number of purportedly involved pathways namely, placental deregulated metabolism of maternal steroids, impaired maturation of fetal HPA axis, imbalanced efflux of commensal bacteria across the placenta, and skewed immune development towards Th2. Fetal programming probably exerts a pivotal role in the end result of the above pathways through the modulation of gene expression. In this review we highlight the current knowledge from epidemiological and experimental studies regarding the effects of MPS on asthma development in the offspring.